Faculty Members' Perspectives on Organisational Identity: Digital Leadership of Universities of Nineveh Governorate - Thabet Ihsan Ahmed; Ahmed Raad Ibrahim; Nour Fares Ahmed; Dhamiaa Ali Abdullah (Indonesian Journal of Physical Education and Sport Science)
Study purpose. This study aimed to identify and determine the level of DL implementation by heads of physical education and sports science departments and the extent to which DL contributes to organisational identity in universities in Nineveh, Iraq. A descriptive survey method was used and the study involved faculty members in colleges and departments.